PERANCANGAN SISTEM INFORMASI PENJUALAN HEWAN TERNAK KAMBING UNTUK AQIQAH DAN QURBAN PADA CV ANUGERAH PRAWIRA GUMILANG FARM BERBASIS WEBSITE - Andru Sandhya Prawira (2022)
Opening a goat farm business is the maintenance and cultivation of goat farm so that they can be sold and become a source of income, especially goat farming companies engaged in aqiqah and qurban services. To expand the livestock sales network, of course, one must have a more effective sales method in order to expand the sales area. The use of manual documents such as recording orders using paper, giving invoices to customers using paper receipts is considered quite dangerous to record incoming transactions because they can be lost, tucked away and so on. Not to mention the method of selling aqiqah and qurban which still uses manual methods such as the buyer having to come personally to the goat stall when buying qurban animals and installing banners and distributing brochures if he wants the aqiqah message to be less effective in attracting buyers. In overcoming this, the author builds a system that uses the waterfall method and UML modeling which is built using a Codeigniter framework and a MySQL database. So, the result of this study is to build a website-based sales information system that can help aqiqah and qurban goat livestock companies to expand sales networks, facilitate buyers and store sales transaction data at CV Anugerah Prawira Gumilang Farm.